2013
DOI: 10.1002/pa.1476
|View full text |Cite
|
Sign up to set email alerts
|

Viral political communication and readability: an analysis of an Italian political blog

Abstract: The Internet is widely used by political parties to report events and to send messages to the voting population. Politicians used digital media (websites, blogs, bulletin boards/lists, and chat/instant messaging) in recent elections, together with traditional media (television, newspapers, rallies, etc.). Political blogs represent not only an additional communication channel but also an instrument for spreading editorial content and messages, virally infecting more traditional media channels. A key task for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…However, this is hardly unexpected of a party that is traditionally elitist (Morrison, 2004). However, since there is some advantage to be gained by using simple language in political communication, the NPP party could benefit from making the language of their manifesto less institutional (Bigi, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this is hardly unexpected of a party that is traditionally elitist (Morrison, 2004). However, since there is some advantage to be gained by using simple language in political communication, the NPP party could benefit from making the language of their manifesto less institutional (Bigi, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Among the variety of online formats available are blogs. Bigi (2013) studied the readability of articles on a blog that had been converted from a personal one discussing political content to a political blog written by a politician. The articles were from January 2005 to May 2012.…”
Section: Linguistic Complexity Of Political Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…Richey (2008) found in his study based on the American National Election Survey data collected in 2000 that social networks of people affect voter behavior. Wattal et al, (2010) In their work on the results of the presidential elections held in the USA in 2008, concluded that Web 2.0 internet-based technologies such as Youtube and MySpace have become an important tool for political candidates in persuading voters (Bigi, 2013).…”
Section: Political Marketing and Viral Communication Interactionmentioning
confidence: 99%
“…Despite the fact that blogs have taken on the role of the new media regarding politics (Savigny & temple, 2010;Donovan, 2012), attracting readers is proving a truly arduous task for a great number of webpages due to the competition which exists to rank highest on Internet search engine lists, and to this end even offering readers unique, interesting content (Drezner & Farrell, 2004) often proves insufficient. Normally, time, consistency and quality of content (Bigi, 2013), control of the message's emotional characteristics (Kim et al, 2015), the social propagation of these messages (to social networks or other similar platforms) and audience interactivity to acquire visibility and relevance regarding the object of interest are all required. Only a reduced number of elite blogs are in a position to become political e-fluentials (Burson Marsteller, 2000;Gill, 2004) and thus condition one issue's greater relevance over another's.…”
Section: The Blog Social Media and Political Communicationmentioning
confidence: 99%